Functional responses of stream fish communities to rural and urban land uses - Miiller,Natali Oliva Roman (2021)
Abstract We tested the effects of ruralization and urbanization on the functional diversity indices and the composition of functional traits of Neotropical stream fish communities. The study was carried out in 24 streams of the Pirapó, Piquiri, Paraná III and Iguassu river basins. Land use in the watershed was categorized as percentages of native vegetation, rural occupation and urban occupation. Statistical tests revealed negative bivariate correlations between functional dispersion and the proportion of native vegetation in the watershed. The results indicate that a higher percentage of rural or urban occupation is associated with increased functional dispersion. In the analyzes of trait composition, significant alterations were observed in response to urbanization while only the increase in herbivory responded to ruralization. As the area of native vegetation is reduced by urbanization, the trait composition changes, with reduced proportions of species with intolerance to hypoxia, migratory reproductive behavior, external fertilization, and subterminal mouth, and increased proportions of species with parental care, detritivory, internal fertilization, and an upper mouth. Therefore, fish species that have these specific characteristics are more likely to disappear from streams as urbanization progresses. In summary, urbanization was related to a greater change in the composition of functional traits than ruralization.